Effects of high-energetic 3He+ ion irradiation on tungsten-based composites. (February 2021) - Demir, E.; Mirzayev, M.N.; Popov, E.P.; Horodek, P.; Genov, I.G.; Siemek, K.; Mirzayeva, D.M.; Turchenko, V.A.; Bulavin, M.; Beskrovnyi, A.I.; Valizade, A.H.; Akhundzada, H.V.; et al.
Abstract: The interaction of plasma and its encompassing materials with one another is one of the principle designing issues of fusion reactors. Tungsten is considered one of the primary candidate materials in fusion applications due to its superior properties. In this work, we doped vanadium carbide powders to the tungsten matrix to enhance the properties of tungsten alloys. Tungsten-based composites, which irradiated with 2.5 MeV 3 He + ions at room temperature, were analyzed by atomic force microscopy (AFM) in order to obtain surface morpohologies after irradiation. Helium ion irradiated tungsten-based composites were studied by using XRD, neutron diffraction technique, raman spectroscopy, and positron annihilation spectroscopy to reveal the microstructural changes. XRD and ND analyses clarified the changes in the crystal structures of the tungsten-based materials after He ion irradiation. The simulation of radiation damage and the calculation of displacements per atom (DPA) was also determined by the SRIM code. SRIM showed that the maximum helium concentration in the specimens takes place in the depth range of 58–65 nm. The crystallite size of tungsten-based composites slightly increased after helium ion irradiation. AFM results revealed that the maximum size of bubbles on the surface of tungsten-based composites shape under 100 nm. Positron annihilation spectroscopy studies of the specimens have been discussed before and after 3 He + ion irradiation. Highlights: Tungsten based sample was irradiated with 2.5 MeV helium ions at the room temperature. The structural characterization of sample was performed XRD, Raman, ND, AFM and PLT. The crystallite size of samples before and after helium ion irradiation as 39.96 nm and 40.39 nm, respectively.